ROS generated from biotic stress: Effects on plants and alleviation by endophytic microbes - Sahu, Pramod Kumar; Jayalakshmi, K.; Tilgam, Jyotsana; Gupta, Amrita; Nagaraju, Yalavarthi; Kumar, Adarsh; Hamid, Saima; Singh, Harsh Vardhan; Minkina, Tatiana; Rajput, Vishnu D.; Rajawat, Mahendra Vikram Singh (Frontiers in Plant Science, 2022)
Aerobic living is thought to generate reactive oxygen species (ROS), which are an inevitable chemical component. They are produced exclusively in cellular compartments in aerobic metabolism involving significant energy transfer and are regarded as by-products.ROS has significant role in plant response to pathogenic stress, but the pattern varies between necrotrophs and biotrophs. A fine-tuned systemic induction system is involved in ROS-mediated disease development in plants. In regulated concentrations, ROS acts as a signalling molecule and activates different pathways to suppress the pathogens. However, an excess of this ROS is deleterious to the plant system. Along with altering cell structure, ROS causes a variety of physiological reactions in plants that lower plant yield. ROS also degrades proteins, enzymes, nucleic acids, and other substances. Plants have their own mechanisms to overcome excess ROS and maintain homeostasis. Microbes, especially endophytes, have been reported to maintain ROS homeostasis in both biotic and abiotic stresses by multiple mechanisms. Endophytes themselves produce antioxidant compounds and also induce host plant machinery to supplement ROS scavenging. The structured reviews on how endophytes play a role in ROS homeostasis under biotic stress were very meagre, so an attempt was made to compile the recent developments in ROS homeostasis using endophytes. This review deals with ROS production, mechanisms involved in ROS signalling, host plant mechanisms in alleviating oxidative stress, and the roles of endophytes in maintaining ROS homeostasisunder biotic stress.